POLA PERTUMBUHAN DAN FAKTOR KONDISI IKAN LELE PANJANG (Clarias leiacanthus ) DI AEK SILOM-LOM, LABUHANBATU - Awendi, Aweng; Machrizal, Rusdi (Jurnal Biosilampari : Jurnal Biologi, 2023)
This study was aimed at analyzing the growth patterns of catfish (Clarias leiacanthus) through the analysis of length weight relationships. The Condition Factor is calculated to determine the habitat conditions of the C. leiacanthus fish population. The research was carried out from October to December 2021 in the Aek Silom-lom River, South Labuhanbatu Regency. Measurement of fish length and weight and identification were carried out at the Ecology Laboratory, Faculty of Teacher Training and Education, Labuhanbatu University. Samples were captured using fishing gear in the form of fishing rods. Growth pattern analysis refers to the Linear Allometric Model (MAL), the condition factor is calculated based on relative weight (Wr) and Fulton (K). The catch during the study was 54 catfish (C. leiacanthus) obtained from Aek Silom-lom. The results of measurements against the sample obtained that the total length range (TL) is 20-31 cm, and weight (W) 81-180 grams. Analysis of the linear allometric model explained that the growth pattern of catfish (C. leiacanthus) is negative allometric b=2.22 (b<3). The results of the condition factor analysis obtained a relative range (Wr) of 81.047 – 124.552 with an average of 88.01. Factor Analysis of Fulton's condition (K) found a K value of 0.84. Based on the value of the Fulton condition factor (K) it can be concluded that the waters of Aek Silom-lom are in a balanced state, and can support the life of long catfish (C. leiacanthus).